Final answer:
The equations 9 - 3x = 0, 2x + 4 = 10, and x/3 + 5 = 6 have the solution x = 3.
Step-by-step explanation:
To find the equation that has the solution x = 3, we need to substitute 3 for x in each equation and see which one gives us a true statement.
Let's substitute x = 3 in each equation:
5x - 7 = 1: 5(3) - 7 = 15 - 7 = 8 (Not true)
9 - 3x = 0: 9 - 3(3) = 9 - 9 = 0 (True)
2x + 4 = 10: 2(3) + 4 = 6 + 4 = 10 (True)
3x + 1 = 9: 3(3) + 1 = 9 + 1 = 10 (Not true)
9x - 1 = 4: 9(3) - 1 = 27 - 1 = 26 (Not true)
x/3 + 5 = 6: 3/3 + 5 = 1 + 5 = 6 (True)
From the above substitutions, we can see that the equations 9 - 3x = 0, 2x + 4 = 10, and x/3 + 5 = 6 all have the solution x = 3.